Uptake of per- and polyfluoroalkyl substances (PFAS) into lettuce (Lactuca sativa), tall fescue (Schedonorus arundinaceus) and tomato (Solanum lycopersicum): A greenhouse experiment evaluating bioconcentration factors and testing the effect of intercropping - Alexandra E. Scearce; Jean D. MacRae; Caleb P. Goossen; Yong-Jiang Zhang; Kylie P. Holt; Rachel E. Schattman (Environmental Advances)
The contamination of agricultural soils with per- and polyfluoroalkyl substances (PFAS), resulting from the application of biosolids and contaminated irrigation water, threatens both human health and the long-term viability of farming operations. While this is a known concern, less is known about factors associated with the transfer of PFAS from soils to crops and how transfer differs across crop compartments and species. The objectives of the present study were to 1) assess bioconcentration factors (BCFs) of lettuce (Lactuca sativa L.), tall fescue (Schedonorous arundinaceus [Screb.] Dumort), and tomato (Solanum lycopersicum L.) grown in a greenhouse using spiked potting mix, and 2) test the efficacy of intercropping as a phytomanagement strategy to influence facilitative and competitive interactions capable of altering PFAS uptake into plants.We found distinct BCFs across species, compartments and compounds. Perfluorobutanoate (PFBA) edible portion BCFs were the highest in tomato fruit, being 3.5-fold higher than in lettuce leaves. For perfluorobutanesulfonate (PFBS), and perfluorooctanoate (PFOA) edible portion BCFs were highest in tall fescue, followed by lettuce, and lowest in tomatoes. BCFs for perfluorooctanesulfonate (PFOS) were not significantly different across species.Across all crop compartments, aboveground BCFs significantly exceeded those of root BCFs (p < 0.05). Intercropped plant pairings only influenced PFBA uptake, reducing uptake of this compound into tomato fruit when paired with lettuce. While other intercropped pairings did alter uptake of PFAS into one or both species compared to monocropped pairings, the directionality of the trend showed that uptake generally increased in intercropped pairings, making this an impractical option for phytomanagement of contaminated agroecosystems.